2011
DOI: 10.1158/0008-5472.can-10-4452
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Blocks Proliferation and Induces Apoptosis of Chronic Lymphocytic Leukemia Cells through Activation of the p53/miR-34a/SIRT1 Tumor Suppressor Network

Abstract: Because of its relatively indolent clinical course, chronic lymphocytic leukemia (CLL) offers a versatile model for testing novel therapeutic regimens and drug combinations. Nicotinamide is the main NAD þ precursor and a direct inhibitor of four classes of enzymes, including the sirtuins. SIRT1, the main member of the sirtuin family, inactivates p53 by deacetylating a critical lysine residue. In this study, we showed that CLL cells express high levels of functional SIRT1, which is inhibited by exogenous nicoti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 48 publications
(53 reference statements)
12
121
2
1
Order By: Relevance
“…Similarly, AzD2281, another PARP inhibitor, in combination with cisplatin synergistically induced cell growth inhibition of breast cancer cells deficient in BRCA2 (24). In agreement with findings of that report, our results demonstrate that the combination of NAM with cis platin significantly decreased cell viability in the three breast cancer cell lines regardless of the BRCA1 status.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, AzD2281, another PARP inhibitor, in combination with cisplatin synergistically induced cell growth inhibition of breast cancer cells deficient in BRCA2 (24). In agreement with findings of that report, our results demonstrate that the combination of NAM with cis platin significantly decreased cell viability in the three breast cancer cell lines regardless of the BRCA1 status.…”
Section: Discussionsupporting
confidence: 92%
“…Chapman et al (28) proposed that SIRT1 is involved in metabolism and tolerance to oxidative stress, promoting the growth of human urothelial cancer cell. Moreover, inhibition of SIRT1 expression reduced cell proliferation even in p53 mutated cells (29). The present study demonstrated that overexpression of miR-34a significantly reduced SIRT1 mRNA and protein expression levels.…”
Section: Discussionsupporting
confidence: 59%
“…Nicotinamide is a known inhibitor of SIRT1, and nicotinamide alters SIRT1-mediated downstream signaling pathways (14,33). However, nicotinamide may inhibit the activity of other sirtuin proteins, including SIRT2-SIRT4 (14,34,35).…”
Section: Discussionmentioning
confidence: 99%